2019
DOI: 10.3928/01484834-20191021-05
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Support Diversity in Nursing Education

Abstract: Background: Despite increased awareness of the importance of cultural competence in the reduction of health care disparities, the nursing profession does not reflect the patient demographics of the United States. The purpose of this article is to report the results of a comprehensive review of the experiences of nontraditional nursing students in undergraduate nursing programs and the interventions used by nursing programs to increase their success. Method: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Multiple funding streams are needed to support enrollment and retention of students of color, particularly those with lower levels of income or education, including scholarships for tuition, books, child care, and other living costs; publicly and privately funded grants; federally‐backed low‐interest loans; and loan forgiveness programs for those who work in underserved areas. 48 , 49 Midwifery schools should redevelop their curriculum to address the interests of students of color in providing holistic care that incorporates traditional or ancestral midwifery practices. Midwifery schools that are committed to addressing racial disparities in health must create a robust pipeline that includes enrolling more students of color; training, mentoring, and paying preceptors of color for their labor; and hiring more faculty of color at all levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple funding streams are needed to support enrollment and retention of students of color, particularly those with lower levels of income or education, including scholarships for tuition, books, child care, and other living costs; publicly and privately funded grants; federally‐backed low‐interest loans; and loan forgiveness programs for those who work in underserved areas. 48 , 49 Midwifery schools should redevelop their curriculum to address the interests of students of color in providing holistic care that incorporates traditional or ancestral midwifery practices. Midwifery schools that are committed to addressing racial disparities in health must create a robust pipeline that includes enrolling more students of color; training, mentoring, and paying preceptors of color for their labor; and hiring more faculty of color at all levels.…”
Section: Discussionmentioning
confidence: 99%
“…Policy interventions to increase diversity in nursing and other health care workforces suggest providing funding to students of color, 48,49 providing culturally‐competent midwifery education, 50,51 creating a robust pipeline for midwives of color, 49,50 and opening more midwifery schools, especially in Historically Black Colleges and Universities, 52 or through collaborations between community and state colleges and private and public entities. Multiple funding streams are needed to support enrollment and retention of students of color, particularly those with lower levels of income or education, including scholarships for tuition, books, child care, and other living costs; publicly and privately funded grants; federally‐backed low‐interest loans; and loan forgiveness programs for those who work in underserved areas 48,49 . Midwifery schools should redevelop their curriculum to address the interests of students of color in providing holistic care that incorporates traditional or ancestral midwifery practices.…”
Section: Discussionmentioning
confidence: 99%
“…10 However, nursing schools and their affiliated institutions also lack sufficient academic and financial support, are inadequately prepared to provide emotional and moral support, and fail to establish the presence of diversity among faculty, leadership, and current students. [11][12][13][14][15] These institutional factors have been commonly identified to complicate attracting and retaining minority students. 15 Moreover, institutional discriminations inhibit effective recruitment, and inherent biases interfere with fair and wholistic admission decisions.…”
Section: Matriculation and Graduation Rates Of Blacks In Nursing Prog...mentioning
confidence: 99%
“…15 Moreover, institutional discriminations inhibit effective recruitment, and inherent biases interfere with fair and wholistic admission decisions. [11][12][13][14][15] A review of strategies in the literature revealed that, to effectively recruit and retain Black students, schools of nursing will need to use interventions that reach diverse student populations and are directed toward promoting a professional presence in the community 8,15 ; building collaborative partnerships [14][15][16] ; supporting an equitable student admissions process 14,[17][18][19] ; providing financial, academic, and emotional support 8,11,13,16,19 ; developing effective communication and cultural empathy among ethnically diverse faculty; and fostering socialization and relationships through mentorship. 12,16,20,21 Recruitment of Black Nursing Students Preentry strategies that establish a professional presence in the community involve educational presentations (eg, career and/or inquiry days) and enrichment programs directed toward elementary, middle, and high school students and their families.…”
Section: Matriculation and Graduation Rates Of Blacks In Nursing Prog...mentioning
confidence: 99%
“…Outside Field (Fontaine, 2014;Jeffreys, 2001;2020a;Kowlowitz, et al, 2018;Kruse, et al, 2020;Schrum, 2015) ᭺ Integrative reviews (Cox, 2019;McNally, et al, 2019) ᭺ Online course retention (DellAntonio, 2017) ᭺ Recruitment, articulation, transfer, and transition for advanced nursing education and career path planning (Jeffreys, 2020a) ᭺ Faculty development and quality improvement for increasing registered nurse (RN) licensing exam pass rates (Curcio, 2019) ᭺ Understanding student perceptions and relationship to other variables (e.g., faculty advisement and helpfulness) (Summers, 2020) In United States (US) national studies (Gamble, 2018;Hoffart, et al 2019) In US statewide studies (Arthurs, 2009;Donnell, 2015;Pence, 2011;Robertson, et al, 2010) Outside the US ᭺ Australia (Pitt, et al, 2012, Pitt, 2013 ᭺ Canada (Craig, 2014) ᭺ Saudi Arabia (Alharbi, 2015;El-Soud, et al, 2017) ᭺ South Africa (Mthimunye & Daniels, 2019) (continued) ᭺ Factor analysis and other results consistent with the underlying NURS framework (Jeffreys, 2007a).…”
Section: Employedmentioning
confidence: 99%